A GIS-Based Analysis for Mapping the Distribution of Seaweed Cultivation Area in East Lombok Southern Coastal Waters - mohammad faisal; Sukuryadi Sukuryadi; Fatma Wulandari (Universitas Sebelas Maret (UNS), 2018)
The analysis employed in geographic information systems is an analysis using GIS (Geographic Information Systems) software as in land mapping or the like. GIS-based analysis can provide information that the potential distribution of seaweed cultivation area owned by the local territory is assuredly propitious; and for that reason, it needs to be maintained wisely for the people welfare. The objectives of this study are to find out the distribution of the potential seaweed cultivation area and to obtain the database on the suitability of seaweed cultivation area in the south waters of East Lombok. This research employs survey approach since it utilizes the existing data for gaining the problem solution rather than hypothesis testing. The instruments deployed in the process of the research are some equipment such as ships, GPS, current kites, measuring signals, thermometer, geological compasses, stopwatch, secchi disk, basic diving equipment, salinometer, and a GIS-based analysis software. The data of the research are carefully collected through observation method, documentation, and experiments. The result of the study shows that the total area of 606.936 ha are classified into suitable category (S2) 47.27%, not suitable area (N) 46.37% and highly suitable area (S1) 6.36%.